THE MAIN STAGES OF DEVELOPMENT OF ELECTORAL LAW AND ELECTION’S SYSTEM IN SWEDEN - I. A. RAKITSKAYA (Московский журнал международного права, 2017)
The article concerns the issues of formation and development of the Swedish election law and electoral system. The author describes the history of the representative body – the Riksdag, that first assembled in the Swedish town of Arboga in 1435; the institution of Riksdag’s four chambers that up till the second half of the 19th century represented various social estates (the nobility, the clergy, the burghers and the yeomanry). The origin of the electoral law in Sweden dates back to early 1800s, when the legislative body was undergoing significant reforms. After the 1866 representative reform, the class-based four-chamber Riksdag was replaced with an elected two-chamber body that represented the country’s entire population. Elections to the upper chamber were held indirectly by the council members of landstings (Swedish counties) and by the  authorized delegates of town councils in larger towns. Riksdag’s second chamber was elected directly by the voters, although high electoral voting qualifications (based on age, income, and gender) remained in place. The article gives special attention to the electoral reforms of the early 20th century, the proclamation of voting rights for all that had been advocated in Sweden for two decades (from 1896 to 1919). These were the reforms that affected the present-day electoral system and election law of this Scandinavian country. It was due to them that the majority system was substituted with the proportional system, age qualifications were lowered and women were granted voting rights. These reforms laid the foundation for the current electoral system and election law of Sweden. The article discusses the outcome of the electoral reformsconducted in the second half of the 20th century. The most significant ones resulted in the transition from bicameralism to unicameralism, and the legislative proclamation of the key principles of election law (universal, equal, free, direct and secret voting rights). The article separately analyses the modern trends of development of the Swedish election law.